2021
DOI: 10.3390/genes12071096
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea—The Good, the Bad and the Ugly

Abstract: Hydroxyurea (HU) is mostly referred to as an inhibitor of ribonucleotide reductase (RNR) and as the agent that is commonly used to arrest cells in the S-phase of the cycle by inducing replication stress. It is a well-known and widely used drug, one which has proved to be effective in treating chronic myeloproliferative disorders and which is considered a staple agent in sickle anemia therapy and—recently—a promising factor in preventing cognitive decline in Alzheimer’s disease. The reversibility of HU-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 144 publications
(200 reference statements)
1
36
0
Order By: Relevance
“…These compounds are small nonnucleosidic molecules that alter the dNTP pools, therefore interfering with polymerase fidelity. Their effects in mutagenesis have been investigated in experiments using gemcitabine [2,2( )-difluoro-2( )deoxycytidine] and clofarabine [(2 S)-2 -deoxy-2 -fluoro-2-chloro-adenosine] as deoxynucleoside analogs (Figure 1) [58][59][60][61]. It has been noted that 5-azacytidine has anti-HIV-1 activity (i.e., EC 50 around 200 nM) and low cytotoxicity, and it has been shown to act in synergy with gemcitabine and resveratrol [62,63].…”
Section: Mutagenic Nucleoside Increase In Mutation Frequencymentioning
confidence: 99%
“…These compounds are small nonnucleosidic molecules that alter the dNTP pools, therefore interfering with polymerase fidelity. Their effects in mutagenesis have been investigated in experiments using gemcitabine [2,2( )-difluoro-2( )deoxycytidine] and clofarabine [(2 S)-2 -deoxy-2 -fluoro-2-chloro-adenosine] as deoxynucleoside analogs (Figure 1) [58][59][60][61]. It has been noted that 5-azacytidine has anti-HIV-1 activity (i.e., EC 50 around 200 nM) and low cytotoxicity, and it has been shown to act in synergy with gemcitabine and resveratrol [62,63].…”
Section: Mutagenic Nucleoside Increase In Mutation Frequencymentioning
confidence: 99%
“…The enrichment of PCNA at leading strands was also detected in cells treated with the DNA alkylating agent methyl methanesulfonate (MMS), which also induces DNA replication stress. [ 71–73 ] This observation prompted us to analyze how PCNA binds to DNA replication forks under normal conditions. We found that PCNA is enriched at lagging strands of DNA replication forks when cells are arrested at G1 by α‐factor treatment and released into S phase at 16°C where DNA synthesis is slowed.…”
Section: Rad53‐mediated Pcna Unloading During Replication Stressmentioning
confidence: 99%
“…A repurposing drug strategy was exploited in trial NCT00485511 where the efficacy and safety of Hydroxyurea (HU) was tested in children with SMN1 - SMN2 mutations. By reducing the need for blood transfusions in patients with sickle cell anaemia, this drug is used for the treatment of chronic myeloid leukaemia as well as in the prevention of painful episodes [ 37 ].…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%